Association of Frailty With Clinical Outcomes in Patients Receiving Primary Prevention Implantable Cardioverter Defibrillators: A Prospective Cohort Study - Dmitry Neymark; Christopher Lee; William F. McIntyre; Maria Higgins; James W. Tam; Colette Seifer (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Frailty predisposes individuals to morbidity and mortality. Increasing numbers of elderly and comorbid individuals are undergoing primary prevention implantable cardioverter defibrillator (ICD) device placement. Little is known about the association of frailty with post‐device implantation outcomes. Methods We conducted a single‐center, prospective cohort study of 71 patients who underwent primary prevention ICD insertion and who had their baseline frailty status assessed using the Fried index. Participants were followed for a median period of 7.8 years. Results The mean age (± SD) was 70.6 ± 4.5 years. 12 (17%) patients met the criteria for frailty. 23 (33%) patients received cardiac resynchronization therapy. Frailty was associated with a significantly higher incidence of mortality (HR [95% CI]; 3.9 [1.2–12.1]), ED visits (2.7 [1.1–6.7]), and hospitalizations (2.8 [1.1–7.6]). Within the non‐frail cohort, there was no association between Fried frailty scores and adverse outcomes. None of the frail patients received appropriate shock therapy. Conclusion Among primary prevention ICD recipients, frailty is associated with worse mortality and morbidity. Clinicians should consider frailty when discussing risks and benefits with this patient population.